The Power of Ritual Weeping as Medium of Dakwah - Dindin Silahudin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2002)
The reinforcement of Islamic morality has been the core objective of every  dakwah activities. In Bandung,  this core objective of dakwah is made more 1 easily realized by the creation of the tradition of ritual weeping. Daarut Tauhid established an indfridual and communal tradition of ritual weeping. This constitutes a novel feature of the variety of dakwah movements and the pesantren tradition at large.As a matter of fact, there may have already existed a tradition of spiritual weeping among muslims mostly among Sufi. However, it is individual in nature and, as a result, is not socially recognized. By means of this weeping, Muslims at Daarut Taubid effectively control their life becoming religiously conscious, they purify themselves from any sin and immorality and pursue the highest standard of piety and righteousness. Tears mean, to them. fear and obedience, submission and relief.